Review article The P2X7 purinergic receptor as a molecular target in bipolar disorder - Gubert, Carolina; Fries, Gabriel Rodrigo; Aguiar, Bianca Wollenhaupt de; Rosa, Adriane Ribeiro; Busnello, João Vicente; Ribeiro, Luciana; Morrone, Fernanda Bueno; Battastini, Ana Maria Oliveira; Kapczinski, Flávio (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2013)
The purinergic system has been increasingly implicated in medical conditions, among them bipolar disorder (BD). This is based primarily on the role of extracellular adenosine triphosphate (ATP) and purinergic receptors in cytokine regulation and the pathological activation of glial cells, leading to neuroinflammation. In addition, adenosine metabolism is directly related to the pathophysiology of BD. Among purinergic receptors, P2X7 was associated with BD in several genetic studies. This particular receptor has a key role in the modulation of the inflammatory response, acting as a sensor of harm and responding to ATP released from injured or stressed cells in the central nervous system, ultimately driving microglial cells from their resting into the activated form. Of note, markers of excitotoxicity and neuroinflammation are significantly upregulated in frontal cortex from BD patients compared with controls, justifying the need for further research. The present review focuses on purinergic signaling in BD, with an emphasis on ATP and adenosine signaling, highlighting the potential role of P2X7R in modulating inflammation and microglia activation in bipolar patients. Due to its ability to act on microglia and modulate neuroinflammation, we believe that more detailed studies of the role of P2X7R in BD are warranted.